1997
DOI: 10.1148/radiology.204.3.9280239
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiomas in children: percutaneous sclerotherapy with an alcoholic solution of zein.

Abstract: Percutaneous sclerotherapy with Ethibloc was a safe and effective procedure in the treatment of macrocystic and mixed lymphangiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(79 citation statements)
references
References 0 publications
1
75
0
3
Order By: Relevance
“…Sclerotherapy has been tried for surgically unresectable lymphangiomas by using intralesional Bleomycin, OK 432 or a percutaneous injection of ethibloc, with successful outcomes [3,7]. Recurrences are known to occur in one-third of cases, regardless of the site of lesion and type of the adjunctive therapy which is given.…”
Section: Resultsmentioning
confidence: 99%
“…Sclerotherapy has been tried for surgically unresectable lymphangiomas by using intralesional Bleomycin, OK 432 or a percutaneous injection of ethibloc, with successful outcomes [3,7]. Recurrences are known to occur in one-third of cases, regardless of the site of lesion and type of the adjunctive therapy which is given.…”
Section: Resultsmentioning
confidence: 99%
“…Many different drugs were used to mimic what may occur spontaneously. The drugs included alcoholic solution of zein (Ethibloc) 10 , acetic acid", fibrin sealant', triamcinolone 13 In 1977 bleomycin, was proposed as a new sclerosing agent for cystic hygroma. 14°' S After that several trials have been reported using bleomycin with good or excellent results in up to 88% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Many adjunctive therapies for treatment of lymphangioma have been described with varying results. Successful outcomes have been reported following the use of intralesional Bleomycin, sclerotherapy with OK432 or percutaneous embolization with Ethibloc [15][16][17] . Local injection of fibrin glue and laser photocoagulation have been used for postnatal treatment 18,19 .…”
Section: Discussionmentioning
confidence: 99%